2010
DOI: 10.1007/s00411-010-0342-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose irradiation causes rapid alterations to the proteome of the human endothelial cell line EA.hy926

Abstract: High doses of ionising radiation damage the heart by an as yet unknown mechanism. A concern for radiological protection is the recent epidemiological data indicating that doses as low as 100-500 mGy may induce cardiac damage. The aim of this study was to identify potential molecular targets and/or mechanisms involved in the pathogenesis of low-dose radiation-induced cardiovascular disease. The vascular endothelium plays a pivotal role in the regulation of cardiac function and is therefore a potential target ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…The higher dose rate used here (190 mGy/ min) induced far more proteome alterations than the low dose rate (200 mGy/min). Bioinformatics analysis indicated that the signalling pathways influenced by the low-dose exposures included are directly dependent on the redox potential and the level of reactive oxygen species [61]. Finally, a recent integrative proteomic and miRNA study showed that a single 200 mGy radiation dose in primary human coronary artery endothelial cells has a significant impact on miRNA expression and consequently protein expression Fig.…”
Section: Biological Mechanismsmentioning
confidence: 98%
“…The higher dose rate used here (190 mGy/ min) induced far more proteome alterations than the low dose rate (200 mGy/min). Bioinformatics analysis indicated that the signalling pathways influenced by the low-dose exposures included are directly dependent on the redox potential and the level of reactive oxygen species [61]. Finally, a recent integrative proteomic and miRNA study showed that a single 200 mGy radiation dose in primary human coronary artery endothelial cells has a significant impact on miRNA expression and consequently protein expression Fig.…”
Section: Biological Mechanismsmentioning
confidence: 98%
“…The rapid development of proteomics methods is reflected in these early studies. The first study using classical two-dimensional difference in gel electrophoresis (2D-DIGE) method could identify only 15 differentially expressed proteins in the irradiated endothelial cell samples compared to nonirradiated controls [3]. The second study with the same endothelial cell line published only a year later (2012) used a combination of 2D-DIGE and stable isotope labeling with amino acids in cell culture and was able to identify more than 3000 proteins of which 136 were differentially regulated [4].…”
Section: Radiation-induced Changes In the Cardiac Endothelial Proteomementioning
confidence: 99%
“…The mechanisms involved are not yet fully understood; however, they appear to be at least partly linked to the transcription factor, nuclear factor (NF)-κB, and the nitric oxide signaling pathway, which in turn mediates various cellular responses, including the secretion of cytokines [such as transforming growth factor (TGF)-β1, interleukin (IL)-6, interferon (IFN)-γ, IFN-β and tumor necrosis factor (TNF)-α] and chemokines (9)(10)(11). Another possible mechanism of radiationinduced cardiovascular alteration, as shown upon low LET radiation (12)(13)(14)(15)(16), is the endothelial retraction and the impairment of cellular adhesion. Matrix metalloproteinases (MMPs), Rho GTPases, calcium signaling and reactive oxygen species seem to be important factors that stimulate modifications in cell junctions and the cytoskeleton through adhesion molecules and actin (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible mechanism of radiationinduced cardiovascular alteration, as shown upon low LET radiation (12)(13)(14)(15)(16), is the endothelial retraction and the impairment of cellular adhesion. Matrix metalloproteinases (MMPs), Rho GTPases, calcium signaling and reactive oxygen species seem to be important factors that stimulate modifications in cell junctions and the cytoskeleton through adhesion molecules and actin (12)(13)(14)(15)(16). Although high LET radiation has been shown to reduce the length of a 3D human endothelial vessel model, both developing and mature (17), only a few studies have been conducted to identify the mechanisms involved in the endothelial response to high LET radiation (18,19).…”
Section: Introductionmentioning
confidence: 99%